Race/ethnicity moderates the associations between lifetime psilocybin use and opioid use disorder - Grant Jones (PLoS ONE, 2025)
Background: Opioid use disorder (OUD) is a debilitating health condition that is associated with significant morbidity and mortality in the U.S. While preliminary studies have demonstrated that psilocybin is associated with lowered odds of OUD, current research in this domain suffers from a lack of investigation into the impact of race/ethnicity on this association. Objective: To assess the impact of race and ethnicity on the association between psilocybin use and lowered odds of OUD using data from the National Survey on Drug Use and Health (2002–2019) (N = 706,891). Method: I used survey-weighted multivariable logistic regression to test whether race/ethnicity moderates the association between psilocybin use and lowered odds of OUD. Subsequently, I stratified my sample by race and ethnicity and assessed the associations between psilocybin and OUD for individual racial and ethnic groups (White, Black, Indigenous, Asian, Multiracial, Hispanic). My analysis plan was pre-registered. Results: Race and ethnicity significantly moderated the association between psilocybin and OUD. Furthermore, when I stratified my sample by race and ethnicity, only White participants and Hispanic participants demonstrated a link between psilocybin and lowered odds of OUD (White aOR: 0.84; Hispanic aOR: 0.68). For Black, Asian, Indigenous, and Multiracial participants, psilocybin did not share a significant association with OUD. Conclusion: Race and ethnicity moderate the associations between psilocybin and OUD. Future longitudinal, experimental, and qualitative research is needed to better understand the pattern of associations I observed in this study.